The role of shopping lifestyle in mediating store atmosphere towards impulse buying - Tengku Putri Lindung Bulan; Riny Chandra (Forum Kerjasama Pendidikan Tinggi, 2023)
This study aims to analyze the effect of store atmosphere on shopping lifestyle, analyze the influence of store atmosphere on impulse buying, analyze the influence of shopping lifestyle on impulse buying, and analyze the role of shopping lifestyle in mediating the relationship between store atmosphere and impulse buying at Suzuya, Langsa City. The population is all consumers of Suzuya Kota Langsa and the sample is 97 respondents. The sample technique uses accidental sampling. Data analysis method using PLS-SEM. The results show that store atmosphere has a positive and significant effect on shopping lifestyle, store atmosphere has a positive and insignificant effect on impulse buying, shopping lifestyle has a positive and significant effect on impulse buying and shopping lifestyle can play a role in mediating the effect of store atmosphere on impulse buying at Suzuya, Langsa City. This research is expected: Suzuya Kota Langsa should add a marketing program to increase customers, and Suzuya Kota Langsa needs to pay special attention when customers start to get confused in the store, because customer convenience is basically the main thing